Wheel of Life, an initial investigation: Topic-Related Polarity Visualization in Personal Stories - Santos, Henrique D. P.; Molin, Greice P. D.; Pinheiro, Jackson; Vieira, Renata (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2017: Anais do XI Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana, 2017)
User-generated content is a rich source of information regarding human behavior in Internet social media. Sentiment analysis is a powerful tool to understand human psychological meanings in text. Visualizing these sentiments and knowledge about users is crucial to figure out the trends in data and to then use this information to make decisions. This work presents an initial investigation about a visualization chart considering topic-related polarities in personal stories by Brazilian bloggers. Visualizing these sentiments allows specialists to rapidly understand user-affected areas of life.